Mangrove PSB:Isolation,Culture and Phosphate-dissolving Ability / 红树林根际解磷菌分离、培养及解磷能力的研究 - 万璐; 康丽华; 廖宝文; 马海宾; 江业根 (Forest research (Beijing), 2004)
Ten phosphate solubilizing bacterial(PSB) strains were isolated from the mangrove rhizospere.The culture condition of the selected most effective strain ZB0211 was examined from 4 aspects.The experimental results showed that the optimal carbon and nitrogen sources were respectively sucrose (10 g·kg-1) and NH4Cl ((1 g·kg-1)),the optimal concertration of NaCl was 1%,and optimal pH 7.5.The potential relationship among pH level,bacterial rowth and phosphate-dissolving ability was also discussed. 本实验从红树林根际分离出不同种类的解磷细菌,经过筛选获得一株解磷能力较强的菌株ZB0211,在纯培养的条件下,对这株解磷菌进行最适培养条件试验。结果表明:碳源以10g·kg-1的蔗糖最佳,氮源以1g·kg-1NH4Cl最好,10g·kg-1NaCl浓度为最适生长浓度,最适初始pH值为7.5。同时进行的解磷能力实验也表明pH值、菌数与解磷能力这三者之间存在一定的相关性。